The Anticipated Hazards Due To Errors In Using Laser In Medicine And Recommendations For The Safe Use Of Medical Laser Systems In Iraqi Hospitals. - Farroha, Azzam S.; Hajim, Khaleel I. (Journal of the Faculty of Medicine Baghdad, 2006)
SummaryOn one hand, laser medical systems are very useful in several medical fields. They are used for diagnosis and treatment. In addition, they are used in medical researches.On the other hand, laser hazards may cause irreversible injuries, especially eye injuries. Therefore the safe use of medical laser systems is very important to protect the laseroperators who are always exposed to laser hazards, and also to protect patients treated by medical laser. This academic research was designed to achieve the safe use of laser medical systems in Iraqi hospitals by:a- Knowing the basic laser concepts. b- Concentrating on the responsibilities of the medical staff that operate the laser units.c- Identifying the anticipated laser hazards to the patients and laser operators.d- Presenting recommendations for the safe use of medical laser systems in Iraqi hospitals.